Impedance of the semi-infinite unraffled cylindrical wave-guide outlet - SNAKOWSKA, A.; WYRZYKOWSKI, R. (Archives of Acoustics, 1988)
The paper presents the exact formula for the impedance of the outlet of a semi-infinite cylindrical wave-guide derived by considering the propagation of an arbitrary Bessel mode towards the outlet and accounting for the generation of all permissible mode due to the diffraction at the open end. For this purpose, the formula of acoustic potential as well as the expressions for the reflection and transformation coefficient were used. The results of numerical calculations of the real and imaginary part and the moduli of impedance for the diffraction parameter ka in the range 0-20 were presented on graphs.